Management of Leadership According to the Principles of Integrity - Siriboot, Kochaporn; Sannato, Phramaha Samrong (Journal of Graduate MCU KhonKaen Campus, 2022)
Administration is the duty of the group leader. It’s both a science and art in working to achieve goals with others by working towards the objectives. Leadership is a state of faith that is accepted and leads others to move or act in the direction that the leader has set. The leadership must have intelligence, goodness and knowledge that lead people to come together and lead them to a good that pretty. Characteristics and qualities of that leadership must have the wisdom to expertise to be dependent on there will educated, smart confident in one’s self, possessing good conduct in act 3 that can control righteous behavior, good intentions, honesty by doing good thing support Aid for the benefit of the people, do not take advantage of others verbal honesty with good words, honesty and proper words to promote unity and reason, honesty with only good thoughts not focus on the way, but only thinking of sacrifice. It is a Buddhist doctrine that give leaders a leadership that consist of Dhamma. It is also to be a good role model for organizations in that society.